The optimization of treatment of patients with community-acquired pneumonia with high cardiovascular risk (case from practice). - V. F. Orlovskii; A. V. Zharkova; S. Ya. Udovichenko (Medičnì Perspektivi)
Pneumonia occupies a significant part in the structure of morbidity and mortality of the population of Ukraine and the whole world. The incidence of this disease is several times higher among elderly patients. At the same time the prognosis for patients of this category can be fairly unfavorable, being connected with a number of age features. This fact, in its turn, points out the necessity of more precise criteria and new methods of assessing changes in the condition of a patient with pneumonia, and it also became a valid criterion to use in determining the severity and prognosis of the disease course. In this article the specific example of the application of the algorithm, named “Integral geriatric evaluation adapted for emergency care”, in the treatment of an elderly patient with pneumonia was considered. The role of statins in the complex treatment of patients with inflammatory diseases and their link with the level of C-reactive protein as a risk indicator of the unfavourable course of the disease in the form of the thrombotic complications was specifieced. So, medical care for elderly patients with pneumonia should be comprehensive in terms of diagnosis (improving the fairness through the application of the new and more precise methodology of assessing the functional state of a human organism) and treatment. The high degree of comorbidity among patients of the category “frail elderly” with pneumonia requires the application of approaches, which enable to reduce the cardiovascular risks and otherones. Such approaches include the administering of statins at high doses, in light of its impact on the level of C-reactive protein as a predictor of the thrombotic complications.